Menelusuri pembelian impulsif: dampak belanja hedonis, gaya hidup belanja, dan pengiriman gratis di kalangan mahasiswa manajemen - Manafe, Leonard Adrie; Wibowo, Bambang Sri; Nugroho, Dodit Cahyo (Universitas Negeri Surabaya, 2025)
This study examines the impact of hedonic shopping, shopping lifestyle, and free shipping on impulse buying among S1 Management students. The research employs a quantitative approach, collecting data through questionnaires directed at students who actively use online marketplaces. The population for this study consists of 4,831 students, while the sample includes 100 respondents selected using probability sampling techniques, specifically simple random sampling. This sample selection is based on the recommendation that a minimum of 30 respondents is necessary to approximate a normal distribution. The distributed questionnaire features five score values to reflect respondents' attitudes toward the research variables. Data analysis was conducted using multiple linear regression, enabling researchers to evaluate the relationships between variables systematically. The results indicated that hedonic shopping and free shipping have a positive but insignificant effect on impulse buying. In contrast, a shopping lifestyle was found to positively and significantly influence impulse buying. This finding suggests that while university students exhibit hedonic shopping tendencies, their impulsive buying decisions are more significantly influenced by their shopping lifestyle. This research provides valuable insights for marketers seeking to understand consumer behavior in the digital age and to develop marketing strategies that align with the characteristics and preferences of young consumers.